Central Nervous System Acting Drugs in Treatment of Migraine Headache - Samsam, Mohtashem (Central Nervous System Agents in Medicinal Chemistry, 2012)
Migraine is a primary headache disorder with an unknown pathophysiology. The growing evidence in recent years indicates migraine being a brain disorder, a sensory dysmodulation, and a system failure of normal sensory processing of the brainstem that involves the vascular tone and pain. At the moment, triptan family and NSAIDs are the first choice drugs for the treatment of acute migraine. There are several prophylactic drugs including the antiepileptic drugs (AEDs), betablockers, and Ca2+ channel blockers that are used for the treatment of migraine. Although many drugs including the triptans, NSAIDs, and others target the peripheral sites of activation, several novel drugs are being developed to target neural sites of action in the central nervous system (CNS). The first trigeminal synapses in the brain stem as well as the ascending and descending pathways and higher brain centers are involved in the transmission of pain and therefore be the main targets of several drugs some of which are in clinical trials. Central sensitization may also aggravate the headache and some drugs tend to alleviate pain by targeting neurotransmitters, receptors, or signalling molecules involved in this phenomenon. This article discusses the CNS acting novel drugs and those that are currently in use for the treatment of migraine.
Keywords: neuronal hyperexcitability